A Middle Dorset Palaeoeskimo structure at Peat Garden North, northwest Newfoundland - Hartery, Latonia; Rast, Timothy (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractDorset Palaeoeskimo sites on ancient gravel and cobble beaches pose exceptional challenges when researching prehistoric dwellings constructed along coastlines. At Peat Garden North, a Middle Dorset Palaeoeskimo site on Newfoundland's Great Northern Peninsula, a feature embedded in a raised dolomite beach is interpreted as a dwelling. Although all that remains of this structure is a poorly defined oval of arranged beach cobbles and gravel, the argument for this feature as a house is based on overall shape, size, internal features, artifact and faunal distribution, and similarities with other houses in the Arctic and sub-Arctic. In conclusion, we suggest that the layout of this house is a function of site seasonality.